Perlindungan Hukum terhadap Boedel Pailit dari Perbuatan Hukum Direksi melalui Gugatan Actio Pauliana - Bintang Adiwangsa; Rilda Murniati; Harsa Wahyu Ramadhan (Lembaga Yasin AlSys, 2026)
The bankruptcy estate constitutes the entirety of the debtor’s assets that serves as the source for the repayment of debts to creditors. In bankruptcy practice, the integrity of the bankruptcy estate is often threatened by the debtor’s legal acts that transfer assets to third parties before a declaration of bankruptcy is pronounced in order to avoid general attachment by the curator. This problem becomes increasingly complex when the debtor is in the form of a Limited Liability Company, because the directors, as the company’s organ, have authority over asset management and are therefore in a position that allows asset transfers to be carried out through seemingly lawful legal acts. This study aims to analyze the application of the actio pauliana lawsuit as a legal instrument in protecting the bankruptcy estate from the legal acts of directors and its legal consequences. This study is normative legal research employing a normative-applied approach through a judicial case study. Data were obtained through library research and document study in the form of statutory regulations and court decisions, which were analyzed qualitatively. The results show that the actio pauliana lawsuit is an effective legal instrument for protecting the bankruptcy estate from the debtor’s legal acts that are detrimental to creditors. All assets transferred by the directors to PT Sinar Mas with the approval of Bank ICBC were declared to be returned to the bankruptcy estate and must be handed over to the curator for the repayment of creditors’ claims. These findings affirm the importance of actio pauliana as a legal protection mechanism for the bankruptcy estate and reinforce the role of the curator in ensuring the recovery of the debtor’s assets for the benefit of creditors.